Izin Lingkungan dalam Kaitannya dengan Penegakan Administrasi Lingkungan dan Pidana Lingkungan Berdasarkan Undang-Undang No. 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup (UUPPLH) - Dewi, Dahlia Kusuma (Hukum Universitas Sari Mutiara Indonesia, 2018)
ABSTRACT Environmental licence based on the Law on Living Environmental Management and Protection (UUPPLH) is a condition to obtain a business licence and/or activity. Functioning as an instrument of damage prevention and/or living environmental pollution in the framework of protecting and managing living environment. Environmental pollution belongs to living creature, substance, energy and/or other components polluted by human activities which is greater than the set standard quality of living environment. A control is needed to monitor the incident of living environmental pollution. Living environmental control or control for short is a sequence of activities which is directly or indirectly by the Living Environmental Controlling Official (PPLH) to find out, to ensure, and to determine the level of compliance of guarantor of business and/or activity set in the evironmental licence and the legislations in the field of living environmental management and protection. The control activity is intended to develop law reinforcement. The reinforcement of administrative environmental law is the control and application of the administrative sanction which are preventive (control) and repressive (administrative sanction) in nature. According to the UUPPLH criminal act is a violation done by an individual on the regulation of legislation and/or the provision of environmental licence. The criminal provision according to the UUPPLH to apply the criminal sanction related to environmental licence as regulated in Article 109, Article 111, and Article 112 of UUPPLH.